2015
DOI: 10.1021/acs.chemmater.5b01744
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Control of Flow in Thin Polymer Films by Photochemically Manipulating Surface Tension

Abstract: The Marangoni effect causes liquids to flow toward localized regions of higher surface tension. In a thin film, such flow results in smooth thickness variations and may represent a practically useful route to manufacture topographically patterned surfaces. An especially versatile material for this application should be able to be spatially programmed to possess regions of higher or lower relative surface tension so that the direction of flow into or out of those areas could be directed with precision. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…These are shown schematically in Figure and will now be treated in turn. As alluded to, other Marangoni methods for polymer patterning, such as photomodification of surface tension or breath figures, while highly promising, are beyond the scope of this review, unless coupled to thermocapillary forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are shown schematically in Figure and will now be treated in turn. As alluded to, other Marangoni methods for polymer patterning, such as photomodification of surface tension or breath figures, while highly promising, are beyond the scope of this review, unless coupled to thermocapillary forces.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the diffusion‐induced solvocapillary flow up thermal gradients that has been observed in FLaSk dewetting of metal alloys discussed above—while such mechanisms are less common polymers, they may be deliberately incorporated. For example, several groups have been exploring the UV‐induced chemical alteration of polymeric systems to trigger subsequent dewetting during melting . Currently, these effects are limited by the homogenization of the film at lengthy heating, which clears the surface pattern.…”
Section: Introductionmentioning
confidence: 99%
“…812 Because the surface tension is a function of several parameters, the introduction of its gradient can be performed through several technological approaches, including the use of vertical or horizontal constant thermal treatment, transverse zone annealing, and so on. 4,1317…”
Section: Introductionmentioning
confidence: 99%
“…The lithographic methods should provide rapid, high-resolution patterning, with high throughput, maximal structure resolution, and an opportunity to control the created structure. , The use of thin polymer film instability represents an elegant way for polymer pattering, which satisfies the above-mentioned requirements. The physical background of thin film instability and related polymer mass redistribution is typically explained within the framework of Marangoni flow, assuming that under the action of a surface tension gradient, a system tends to evolve toward a stable state by minimizing its surface area through the material flow. , The Marangoni-driven mass redistribution was successfully applied to create self-assembled polymer structures and the structures with arbitrary symmetry and, more recently, for the nanoscale removal of a protective thin film by resistive heating of carbon nanotubes. Because the surface tension is a function of several parameters, the introduction of its gradient can be performed through several technological approaches, including the use of vertical or horizontal constant thermal treatment, transverse zone annealing, and so on. , …”
Section: Introductionmentioning
confidence: 99%
“…The authors identified decarboxylation and dehydrogenation reactions as the chemical processes driving the flow. 75 …”
Section: Introductionmentioning
confidence: 99%